Caregivers’ experiences of providing care to female patients in Swedish forensic psychiatric care - Revelj, Jessica; Hörberg, Ulrica; Wallinius, Märta; Rask, Mikael (Frontiers in Psychiatry, 2025)
IntroductionA core element of caring science, is for caregivers to understand and collaborate with patients. Previous research shows that women receiving forensic psychiatric care evoke strong emotions among caregivers, but there is little research on the subject, and increased knowledge about caregivers’ experiences of providing care for female patients in forensic psychiatry, and of balancing healthcare with public safety considerations, is needed for the continued development of evidence-based care.MethodThis qualitative study aimed to describe and gain a greater understanding of caregivers’ experiences of providing care for female patients in forensic psychiatric care. The study is based on 14 interviews with caregivers working with female patients at four forensic psychiatric clinics. The data were analyzed using a phenomenological hermeneutical method, which is suitable for researching lived experiences. The analysis was conducted in accordance with the method described by Lindseth and Norberg and revealed that caregivers emphasized the importance of being present in relation to the women.ResultsThe following themes emerged: Providing care that is responsive to the conditions in forensic psychiatric care, Being an individual in a caring relationship, Providing support and strength, and Allowing the patient’s needs to determine the course of the care. The women were perceived as less physically strong than male patients but engaged in acts of violence against themselves and others. This could result in coercive measures that could also be experienced as uncomfortable for the caregivers, particularly when having to restrain the women.